Consumers' willingness to pay for organic versus all‐natural milk – Does certification make a difference?. (23rd October 2020) - Yormirzoev, Mirzobobo; Li, Tongzhe; Teuber, Ramona
Abstract: While there is ample evidence on consumers' perceptions and willingness to pay (WTP) for organic food in developed markets, empirical evidence for transition economies is scarce. This paper is based on a survey of 608 Russian consumers that combined a questionnaire with a contingent valuation approach to investigate the impact of perceptions and trust on consumers' WTP for certified organic, uncertified all‐natural and conventional milk, respectively. A between‐subject treatment design was used to analyse how consumers' WTP responds to different information treatments. Our results suggest that most participants connect health benefits with the consumption of organic food, followed by slightly fewer respondents connecting organic production with environmental benefits. In the case of animal welfare benefits, the picture is less clear, as only 46% of respondents indicated that they agree that organic livestock production is associated with animal welfare benefits. Concerning the trust in farmer's adherence to organic standards, a substantially higher share of respondents expressed trust in producers from the European Union versus their Russian counterparts. About 51% of respondents exhibited a positive WTP for organic milk in comparison to conventional milk. At the same time, there is no statistically significant difference in respondents' WTP between all‐natural and organic milk. This similarity suggests that respondents do not seem to differentiate between uncertified all‐natural milk and certified organic milk.